Anatomical and functional responses to single brolucizumab injection in neovascular age-related macular degeneration patients not responding to antiangiogenics: a case series - Silvio Zuccarini; Fabrizio Puce; Alessandro Crisà (AboutScience Srl, 2022)
Introduction: Neovascular age-related macular degeneration (nAMD) is treated with antivascular endothelial growth factor (anti-VEGF) drugs. However, resistance to anti-VEGF therapy is observed in some patients. Brolucizumab is a new-generation anti-VEGF drug for the treatment of nAMD, with proven efficacy in fluid resolution and long-lasting effects. Methods: We report here a case series of nAMD patients not responding to previous anti-VEGF therapy showing anatomical and functional response to a single intravitreal injection of brolucizumab. Results: Nine patients with nAMD, undergoing treatment with anti-VEGF therapy (aflibercept, bevacizumab, or ranibizumab) but with either fluid persistence or frequent fluid recurrences in retinal compartments, were switched to intravitreal brolucizumab and examined 4 weeks postinjection. No signs of active disease were observed in all but one patient, with complete retinal fluid resolution in seven patients. Central macular thickness and visual acuity significantly improved, and changes were sustained for up to 12 weeks in a subset of three patients. No adverse reactions were observed. Conclusions: This new anti-VEGF drug showed great efficacy since the first week from the injection with a significative reduction of subretinal fluid and rapid improvement of visual acuity. In conclusion, brolucizumab administered intravitreally appears to be an effective treatment in nAMD patients, leading to both early anatomical and functional improvements.